1996
DOI: 10.1210/jcem.81.5.8626868
|View full text |Cite
|
Sign up to set email alerts
|

Molecular scanning of the insulin receptor gene in women with polycystic ovarian syndrome.

Abstract: Polycystic ovary syndrome (PCOS) is a common disorder characterized by chronic anovulation and infertility, hyperandrogenaemia, and frequently insulin resistance. This study investigated whether mutations in the insulin receptor gene could explain the insulin resistance in subjects with PCOS. From a total of 108 women with PCOS, a subgroup of 24 were selected on the criteria of being in the upper quartile for insulin resistance as assessed by fasting serum insulin, insulin area under the curve following 75 g o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
1
3

Year Published

2001
2001
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 29 publications
1
17
1
3
Order By: Relevance
“…The hypothesis for the existence of a postreceptor defect in insulin action in PCOS is also consistent with reports of molecular studies found no structural abnormality in the insulin receptor (Conway et al ., 1994;Sorbara et al ., 1994;Talbot et al ., 1996).…”
Section: Insulin Resistancementioning
confidence: 99%
“…The hypothesis for the existence of a postreceptor defect in insulin action in PCOS is also consistent with reports of molecular studies found no structural abnormality in the insulin receptor (Conway et al ., 1994;Sorbara et al ., 1994;Talbot et al ., 1996).…”
Section: Insulin Resistancementioning
confidence: 99%
“…Other studies showed that the number and affinity of insulin receptor is not altered in PCOS but its tyrosine phosphorylation status and subsequent signaling is affected, suggesting the defect may lie in the b-chain (16,20). Studies to determine mutations in INSR failed to find any major variations; however, several polymorphisms were identified (21)(22)(23)(24)(25)(26)(27)(28). The most frequent of these were at exon 17, which encodes the partial tyrosine kinase domain containing the ATP binding site of INSR, important for its downstream signaling (21)(22)(23)(24)(25)(26)(27)(28).…”
Section: Introductionmentioning
confidence: 99%
“…Studies to determine mutations in INSR failed to find any major variations; however, several polymorphisms were identified (21)(22)(23)(24)(25)(26)(27)(28). The most frequent of these were at exon 17, which encodes the partial tyrosine kinase domain containing the ATP binding site of INSR, important for its downstream signaling (21)(22)(23)(24)(25)(26)(27)(28). Among these polymorphisms, a C/T SNP at His1058 in exon 17 has been reported to be significantly associated with PCOS in two independent studies in Caucasian and Chinese women (25,26).…”
Section: Introductionmentioning
confidence: 99%
“…PCOS is another good model to study influent genes, because in this complex disease, characterized by chronic anovulation and hyperandrogenism in women, insulin resistance is a major component (3,12). In common forms of PCOS, IR mutations have not been found, and linkage studies excluded IR and IRS-1 as major genes (13,14). To understand genetic determinants of insulin resistance, we investigated the effects of two variants of IRS-1 and IRS-2 in PCOS (n ϭ 53) with values (mean Ϯ SE) for homeostasis model assessment index for insulin resistance (HOMA IR ) twofold higher than the control population (1.56 Ϯ 0.034, n ϭ 102) ( Table 1).…”
mentioning
confidence: 99%